Optimizing Arm Muscle Endurance in Pencak Silat Athletes: Insights from a Literature Review - Nubatonis, Jefrio Demitrimus; Sulistiyono, Sulistiyono; Husein, Muhamad; Septianto, Irvan; Runesi, Salmon; Zakiah, Dwi Manna Nazmi; Dewantara, Julian; Azrina, Jihan; Islam, Syahrizal; Salacup, Vince Louisse D. (Universitas Tanjungpura, 2024)
Background and Study Aim. Pencak Silat is a martial art that demands exceptional physical strength, agility, and endurance. Among these, arm muscle endurance plays an important role in performing effective offensive and defensive maneuvers. Improving arm muscle endurance not only enhances technical efficiency but also minimizes fatigue and prolongs performance during matches. This study aims to explore and analyze proven strategies and methods to optimize arm muscular endurance in Pencak Silat athletes.Materials and Methods. This study used a literature review approach to investigate findings related to improving arm muscular endurance in Pencak Silat athletes. The research process involved a systematic search of electronic databases, including Google Scholar, PubMed, and ScienceDirect, using specific keywords such as